Successful Aging of Elderly People in Low Economic Status Who Are Still Working and it is Related To Daily Activities and Hardiness - Felizarda Menezes Amaral; Christiana Hari Soetjiningsih (Universitas Katolik Soegijapranata, 2019)
Raising the age of life expectancy has its impact on the increasing number of elderly people, and it is expected that they can achieve successful aging including those who are in low economic status and still working. The aim of this quantitative research is to examine the effect of daily activities and hardiness simultaneously toward successful aging of elderly people in low economic status who are still working. The research participants were 120 elderly people who lived in Central Java (Salatiga, Semarang, Surakarta, Magelang, Pekalongan, and Tegal) with the characteristic aged of 60 and over, communicative, and they were willing to be participants. The sampling technique used was purposive sampling. The data was obtained using Daily Activity Scale, Hardiness Scale and Successful Aging Scale. This data was analyzed using statistical techniques of multiple linear regression, with the results of F = 45,329 and a significant value of 0.00 (p